Acute effect of foam rolling on rate of force development in the vertical jump - Wee, Jericho Faliang (2018)
Background: Foam rolling is a popular modality used by practitioners to break up fibrous adhesions in connective tissue and increase muscle length. There is little supporting evidence that foam rolling influences performance. Purpose: To investigate the effects of foam rolling on the rate of force development (RFD) in the countermovement vertical jump. Method: 17 males (age 23.9 ± 0.9; height 1.72 ± 0.04 cm; mass 69.9 ± 7.5 kg) completed a day of familiarisation, followed by three days of testing. Participants performed a dynamic-warm up, followed by 30-second bouts of unilateral foam rolling on the lower body with a hard (DW-HFR) or soft foam roller (DW-SFR); or no foam rolling (DW). The highest RFD of three jumps for each testing was used for statistical analyses. Results: One-way repeated measures ANOVAs of RFD revealed no significant differences between conditions, F (2,32) = .098, p = .826, ƞ2 = 0.00023. Secondary performance measures had insignificant differences (p >.05) between conditions for pairwise and omnibus comparisons. Conclusion: Dynamic warm-up using hard or soft foam roller has no effect on vertical jump performance in terms of RFD, peak power, peak velocity, peak force, and jump height; compared to dynamic warm-up on its own.